Repeat Cesarean Section: A Major Risk Factor for Peripartum Hysterectomy - Saira Yunus; Bushra Bano; Shamila Tasneem; Amtullah Zarreen (Pakistan Journal of Medical Research, 2021)
Background: The overall annual incidence of caesarean delivery in Pakistan has been steadily rising over the past two decades from 14% in 2012-13 to 22% in 2017-18. Primary caesarean often leads to repeat caesareans, which may result in increased chances of morbid adherence of placenta. Now it has become proportionally a major cause of maternal morbidity and mortality.